Integrated multi-criteria evaluation of house's plan shape based on the EDAS and SWARA methods. Issue 3 (3rd July 2017) - Juodagalvienė, Birutė; Turskis, Zenonas; Šaparauskas, Jonas; Endriukaitytė, Audronė
Abstract: With this article we strive to create a theoretical valuation model based on multiple criteria mathematical methods by selecting a basic shape of single-family residential house's plan. Most of the researches and analysis discuss the interfaces of architectural shapes of the buildings with sustainability only in the buildings with unique design. Meanwhile, the model comprising a selection of a basic shape of the single-family house was not implemented. Our study evaluated the individual parameters associated with selection of the house shape: compactness, safety, material input, variability of premises and spaces. The SWARA (Step-Wise Weight Assessment Ratio Analysis) method is applied in the calculation of the relative importance of the criteria and the EDAS (The Method of Evaluation Based on Distance from Average Solution) method was used to prioritize the alternatives.